(untitled) (University Heart Journal, 2009)
Â A thirty years old lady presented with uncontrolled hypertension and dizziness during working for last 5 years. She had history of termination of pregnancy due to treatment-resistant hypertension. Even in the post-partum period her blood pressure remains uncontrolled with more than three antihypertensive drugs. Her serum K+ level was low and USG of KUB & adrenal glands showed slightly increased right renal cortical echotexture; CT scan of abdomen revealed right Adrenal adenoma. She underwent unilateral adrenalectomy. Now, she has no complaints and her blood pressure is normal without any antihypertensive drugs. There is no target organ damage. Key words: Primary hyperaldosteronism, unilateral adrenal adenoma, resistant endocrine hypertension Â doi:10.3329/uhj.v4i2.2077 University Heart Journal Vol. 4 No. 2 July 2008 p.49-50